The Correlation Between Archetype Personality and Business Success in Small & Medium Enterprises in Java Island - Wikantiyoso, Bimo; Riyanti, Benedicta Prihatin Dwi; Suryani, Angela Oktavia; Soeharso, Sonny (Journal of The Community Development in Asia, 2024)
Intense competition and unpredictable conditions have made problem-solving more challenging. Unlike the relatively stable markets of the 20th century, today's world is characterized by VUCA: volatility, uncertainty, complexity, and ambiguity. SMEs, which make up the majority of businesses globally, are particularly affected by these changes. Entrepreneurs, as the driving force behind SMEs, play a crucial role in both developing and developed economies. Their contributions significantly impact economic growth, as recognized by governments. Research indicates that personality traits can accurately predict business behavior and success, emphasizing that entrepreneurship is a dynamic process requiring continuous effort to deliver products or services that bring financial and personal rewards. The archetype approach, which explores personal dynamics and environmental interactions, provides insights into entrepreneurial success. Archetypes represent patterns of perception, memory, and action that align with ancient motivational and emotional systems, helping to explain how the mind navigates social complexities. The Hero's Journey as an archetype framework offers a valuable perspective on personal development in a career context, addressing universal human motivations across cultures.